Solusi Termudah Mengatasi Bendungan ASI dengan Terapi Pijat Oketani - Wahyuningsih; Emi Sutrisminah (INVOLUSI: Jurnal Ilmu Kebidanan, 2020)
Failure in the breastfeeding process often occurs because of several problems that arise in post-partum mothers, including the lack of fluency in the milk found in cases of breast milk damaging. Dams of ASI (Breast Engagement) are caused by increased venous flow from lymph in the breast which causes a feeling of fever, redness, swelling and hardening. One of the treatments that can be done to improve lactation problems and make it easier for babies to suck breast milk is by using oketani massage. Oketani massage can stimulate the strength of the pectoralis muscles to increase milk production and help the consistency of the breasts to become elastic. The aim of this study was to determine the relationship between oketani massage and increased milk production in mothers with breast congestion. The method used is literature study. The research results were obtained from several sources of research data. The conclusion of this study is that there is a relationship between oketani massage and the amount of milk production in post partum mothers.